Chromosome 1p36.22p36.21 duplications/triplication causes Setleis syndrome (focal facial dermal dysplasia type III). (27th February 2015) - Weaver, David D.; Norby, Audrey R.; Rosenfeld, Jill A.; Proud, Virginia K.; Spangler, Brooke E.; Ming, Jeffrey E.; Chisholm, Elizabeth; Zackai, Elaine H.; Lee, Beom Hee; Edelmann, Lisa; Desnick, Robert J.
<x xml:space="preserve">Abstract</x> Focal facial dermal dysplasias (FFDD) are characterized by congenital bitemporal or preauricular atrophic skin lesions, and either autosomal dominant or autosomal recessive inheritance. Setleis syndrome (SS), FFDD type III, is a severe form of FFDD with the ectodermal lesions plus other striking facial features. Autosomal recessive nonsense and frameshift mutations in TWIST2 have been found to cause SS in some but not all individuals. Here, we report on four unrelated individuals, one with an unclassified FFDD and the other three with classic SS. Chromosomal microarray analyses revealed unique copy number variants of 1p36 in two individuals with duplications at 1p36.22p36.21 and one with a triplication at 1p36.22p36.21. The fourth patient had normal chromosomes by microarray analysis. All four patients had normal TWIST2 exonic sequences. We propose that a dosage effect of one or more of the 30 genes in the 1.3 Mb 1p36.22p36.21 region of overlap is responsible for FFDD/SS manifestations in some individuals, and this mechanism would be inherited as an autosomal dominant trait. In patients with no duplication/triplication of the 1p36.22p36.21 region and no mutations in TWIST2, there are mutation(s) in one of the 30 genes in this region or mutations in other as yet unidentified genes at different locations that may affect the expressions of genes in this region or act independently to cause this developmental disease phenotype. © 2015 Wiley Periodicals, Inc.